2011
DOI: 10.1016/j.jaac.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Child and Family Influences on Maternal Expressed Emotion Toward Children With Attention-Deficit/Hyperactivity Disorder

Abstract: Objective: We used multi-level modelling of sib-pair data to disentangle the influence of child-specific and shared family influences on maternal expressed emotion (MEE) towards children and adolescents with attentiondeficit/hyperactivity disorder (ADHD). Method: MEE was measured for 60 ADHD proband-unaffected sibling pairs aged 6-17 years using the Five Minute Speech Sample. Questionnaire measures of conduct and emotional problems were collected for children and measures of depression and ADHD were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 53 publications
2
43
1
2
Order By: Relevance
“…In this case the null findings would be expected. However, since evidence has been found for both parent effect [44,45] and child effect models [46,21], it is more likely that both causation models are valid and complementary in capturing the underlying mechanisms. Third, if reverse causation plays a role, the model could become even more complicated if we take into account that mothers could be differentially susceptible to environmental experiences, in this case their children’s behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In this case the null findings would be expected. However, since evidence has been found for both parent effect [44,45] and child effect models [46,21], it is more likely that both causation models are valid and complementary in capturing the underlying mechanisms. Third, if reverse causation plays a role, the model could become even more complicated if we take into account that mothers could be differentially susceptible to environmental experiences, in this case their children’s behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who belong to the same group are under influence of shared stimuli, which may have different impacts on their own personal characteristics and multilevel analyses provide estimates of the influence of each explanatory variable for parental symptoms on offspring symptoms regarding ADHD, anxiety and depression. A few studies [23][24][25][26] have used multilevel analysis in ADHD, however, they have not used Bayesian procedures for the multilevel model analysis as in the present study. Other researchers have used Bayesian procedures but not in family-based epidemiological genetic studies [27,28].…”
Section: Methodsmentioning
confidence: 99%
“…Cartwright et al [23] investigated the indirect correlations between maternal depressive symptoms and ADHD diagnoses in children using multilevel analyses to investigate the role of an individual variable (ADHD categorical diagnosis) and a family variable (maternal depressive symptoms) on scores of Maternal Expressed Emotions (MEE). Their results showed a significant influence of maternal depressive symptoms on their children's ADHD condition on the MEE.…”
Section: Parental Adhd Symptoms and Offspring Anxiety And Depressionmentioning
confidence: 99%
“…In other words, similar parental attitudes may have different influences on different children. Cartwright et al [43] also found that negative maternal emotions expressed towards children with ADHD (e.g., low warmth and hostility/criticism) are more damaging than emotions expressed towards children without ADHD. In this case, in addition to the impact of negative parenting on behavioral problems in children, it is important to also consider the influence of children’s behavioral problems on parents’ attitudes.…”
Section: Discussionmentioning
confidence: 99%